Participação dos neurônios catecolaminérgicos do tronco encefálico no controle respiratório - Patrone, Luis Gustavo Alexandre (2015)
It is well know that the respiratory network, undergoes significant development in the postnatal period. Among various processes, the maturing of the catecholaminergic (CA) system shows to be an important factor in the control and modulation of respiratory rhythmogenesis. Studies have also shown that these neurons are widely distributed in the Central Nervous System (CNS), including the A1/C1, A2/C2, C3, A5, A6 and A7 regions, having numerous projections to many regions of the brain. However, the development of respiratory network as well as its effect on the control of ventilation, is not yet fully understood. Thus, understanding the participation of CA neurons in the respiratory control during postnatal development is of most importance for a better understanding of some clinical disorders including Rett Syndrome, Sudden Infant Death Syndrome (SIDS) and Central Congenital Hypoventilation Syndrome (CCHS). Therefore, this study aimed to investigate the involvement of CA neurons in the brainstem on respiratory control in normoxic normocapnic, hypercapnic and hypoxic conditions during the postnatal period of male and female neonatal rats, through chemical injury with conjugated saporin anti-dopamine beta-hydroxylase (DBH-SAP). Thus, DBH-SAP (42 ng/100 nL – 1L), saporin (SAP – 1L) or phosphate buffered solution vehicle (PBS, 0.01M, pH 7.4 – 1L) were injected into the 4th ventricle in male and female neonates Wistar rats P0-1. Pulmonary ventilation ( EV ) was recorded in unanesthetized neonates (P7-8) by pressure plethysmography during normocapnia, hypercapnia (7% CO2) and hypoxia (10% O2) at 10 and 20 min after the start of exposure. Our data demonstrate that lesion of brainstem CA neurons increased ventilation in males and females newborn under room air conditions. In addition, the ventilatory response to hypercapnia was significantly reduced in male (57%) and female (55%) lesioned neonatal rats (Male – SAP group: 212.8 ± 7.0; PBS group: 203.9 ± 10.3; lesioned group: 151.1 ± 7.4; P < 0,001; Female – SAP group: 218.2 ± 10.4; PBS group: 200.0 ± 6.4; lesioned group: 154.0 ± 9.6; P < 0,001; all values relative to % of baseline). Also, a similar reduction was observed in the hypoxic condition (Male – SAP group: 185.2 ± 15.3; PBS group: 167.4 ± 5.0; lesioned group: 110.8 ± 9.2; P < 0,001; Female – SAP group: 197.3 ± 11.8; PBS group: 179.5 ± 13.7; lesioned: 129.4 ± 5.9; P < 0,001; all values relative to % of baseline). Additionally, the values for metabolic rate of control and lesioned groups, both males and females, did not differ significantly, whether in normoxic normocapnic, hypercapnic or hypoxic conditions. These results suggest that brainstem CA neurons exert a tonic inhibitory role in neonatal ventilation and promote an important excitatory modulation in CO2 and O2 chemosensitivity in unanesthetized males and females neonatal rats (P7-8).